Insomnio, ansiedad y depresión en el paciente oncológico - Maté, Jorge; Hollenstein, María F.; Gil, Francisco L. (Psicooncología, 2004)
The presence of psychiatric disorders in the cancer patient has been well documented. In spite of their frequency, the identification of these disorders remains insufficient. There are various reasons for this, such as: a) the mingling of somatic and psychological symptomatology; b) believing that the presence of anxiety, depression, or insomnia is normal among patients with cancer; c) the lack of training of medical personnel in the detection of psychiatric disorders; or d) viewing these disorders as secondary to the illness itself and to the oncological ¡ treatments. This research paper deals with insomnia, anxiety, and depression among cancer patients, as being the disorders with the highest incidence among them and with the greatest impact on their well-being. We present guidelines for the detection of these disorders, as well as their pharmacological and non-pharmacological treatment